Progestins used in endocrine therapy and the implications for the biosynthesis and metabolism of endogenous steroid hormones. (5th February 2017) - Louw-du Toit, Renate; Storbeck, Karl-Heinz; Cartwright, Meghan; Cabral, Angelique; Africander, Donita
Abstract: Steroidogenesis refers to the de novo synthesis of steroid hormones from cholesterol by a number of sequential enzyme catalysed reactions in the adrenal and the gonads. In addition, circulating steroid hormone precursors are further metabolised in selected peripheral tissues. It has been suggested that the biosynthesis of endogenous steroid hormones can be modulated by progestins, used widely by women in female reproductive medicine. However, as a number of structurally diverse progestins with different pharmacological properties are available, it is possible that these synthetic compounds may vary in their effects on steroidogenesis. This review summarises the evidence indicating that progestins influence the biosynthesis of steroid hormones in the adrenal and gonads, as well as the metabolism of these endogenous hormones in the breast, highlighting the limitations to the current knowledge and directions for future research. Highlights: Human studies examining the effects of progestins on steroidogenesis are lacking. Available studies are mostly from animal models or in vitro cell culture. Progestin effects on steroid biosynthesis are dependent on type and concentration. Progestins exhibit species- and tissue-dependent effects on steroid biosynthesis. Most studies investigate the effects of only medroxyprogesterone acetate.